Teachers' Reflective Thinking on Their Professional Experiences - Cennet Tandırcı; Serkan Ünsal; Reyhan Ağçam (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
The existing literature on the teachers’ professional development informs that teaching experiences contribute both to their professional learning and development and student achievement. Yet, the research on the reflection of these experiences over their professional development is rather scarce. Hence, this qualitative study was an attempt to investigate teachers’ reflective thinking on their professional experiences. Participants of the study were a group of experienced teachers teaching various subjects at Turkish state schools who were selected via the purposive sampling. The research data were gathered with a semi-structured interview form developed by the researchers following an extensive review of literature, and administered to content analysis. The results showed that teacher professionalization is largely governed by their experiences which increase the quality of their work and enable them to focus on success. It was also revealed that teachers question their previous professional lives with their current professional experiences and make reflective thoughts about their professional life. The research ends with a couple of practical implications generated based on the obtained results and a few suggestions for future directions